Uso de cadeias de Markov para identificar atribuições em mídias digitais - Carvalho, Raquel Malheiro de (Universidade Federal de São Carlos, 2022)
With the advancement of digital marketing and the rise of new paid media channels for running campaigns and ads aimed at selling products, many advertisers question the use of media that do not directly lead to conversions, meaning the user does not convert through them. Therefore, statistical methods can be employed to identify the role of each media channel in conversions, considering user behavior leading up to the conversion. In this work, Markov Chains are used as a method to analyze user behavior in digital media by estimating user conversion probabilities.
Using Markov chains to identify attributions in digital media
Keywords: Cadeia de Markov; Marketing digital; Probabilidades de transição; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::INFERENCIA EM PROCESSOS ESTOCASTICOS